A comparison between veterinary small animal general practitioners and emergency practitioners in Australia. Part 2: client-related, work-related, and personal burnout - Li, Kun; Mooney, Erin; McArthur, Michelle; Hall, Evelyn; Quain, Anne (Frontiers in Veterinary Science, 2024)
Burnout is reported to be common among veterinarians. However, there is limited research investigating the relationship between specific types of veterinary practice and burnout. A previous study found significant differences in work exposures between veterinary general practitioners (GPs) and emergency practitioners (EPs). The primary aim of this study was to investigate whether Australian veterinary EPs suffer from a higher level of burnout compared to veterinary GPs. The secondary aim of this study was to explore if the previously reported differences between GP and EP groups were positively associated with burnout. An anonymous, online survey incorporating the Copenhagen Burnout Inventory (CBI) was administered to veterinary GPs and EPs practicing in metropolitan regions of Australia. In total, 320 responses were analysed (n=237, 74.2% GPs and n=83, 25.9% EPs). Both groups suffered from moderate levels of burnout, but there were no significant differences in the severity of CBI burnout scores between the two groups. From the multivariable analysis four investigated factors were found to be significantly associated (P<0.05) with the work-related CBI subscale: frequency of finishing work on time; adequate staffing; work satisfaction and seriously considering leaving their principal area of practice. Five factors were significantly associated (P<0.05) with the client-related CBI subscale: position in practice; frequency of client adherence; work satisfaction; frequency of interacting with emotionally distressed clients and seriously considering leaving their principal area of practice. Four factors were significantly associated (P<0.05) with the personal burnout CBI subscale: gender; seriously considering leaving their principal area of practice; frequency of interacting with emotionally distressed clients and the workplace environment. The total burnout score was also significantly associated (P<0.05) with four factors: position in practice, workplace environment, appropriate staffing in the past week and client adherence. Future studies should focus on investigating effective strategies to mitigate these risk factors for both GPs and EPs, to reduce career attrition.